Teacher Pedagogical Competence and Students' Listening Skill: Learning Attitude as an Intervening Variable - Yunita Sari adelina; Neneng Sri Lestari; Syarifah; Fernando De Napoli Marpaung (English Lecturers and Teachers Association (ELTA), 2026)
This study aims to analyze the effect of teacher pedagogical competence on students' English listening skill with learning attitude as an intervening variable among Grade XI students of SMK Al-Maksum, Langkat Regency. The type of research used is quantitative associative using the Structural Equation Modeling (SEM) method based on Partial Least Square (PLS) with the help of SmartPLS version 3.0 software. The population in this study includes all eleventh-grade students within the SMK Al-Maksum organization, totaling 53 students. Sampling applied a saturated sampling technique (census), so that all 53 population members were involved as active respondents. The results of direct effect hypothesis testing show that teacher pedagogical competence has a positive and significant effect on students' learning attitude (original sample = 0.895; T-statistics = 24.629; P-values = 0.000). Similarly, students' learning attitude recorded a strong positive and significant effect on students' listening skill (original sample = 1.187; T-statistics = 4.814; P-values = 0.000). Conversely, teacher pedagogical competence is proven to have a negative and non-significant direct effect on students' listening skill (original sample = -0.369; T-statistics = 1.358; P-values = 0.180). In mediation effect testing, students' learning attitude is significantly proven to act as a full mediator that bridges the influence of teacher pedagogical competence on students' listening skill (original sample = 1.062; T-statistics = 4.274; P-values = 0.000). The adjusted R-square values indicate that pedagogical competence accounts for 79.6% of the variance in learning attitude , while the model's capability to predict listening skill variance accounts for 75.3%, which falls into a strong category. Keywords : Pedagogical Competence, Learning Attitude, Listening Skill